Implementation of the Independent Curriculum through Project for Strengthening Pancasila Student Profilesto FKIP PBSI Al Washliyah Muslim University Medan Students - Fatria, Fita; Husna, Tiflatul; Purba, Alfitriana (West Science Interdisciplinary Studies, 2024)
This research aims to implement the Independent Curriculum through the Project for Strengthening the Profile of Pancasila (P5) Students Based on Character Education for FKIP PBSI Students at Al Washliyah Muslim Nusantara University, Medan. Bearing in mind that student character formation must be improved through the P5 independent curriculum program. The project to strengthen the Pancasila student profile, as a means of achieving the Pancasila student profile, provides students with the opportunity to "experience knowledge" as a process of strengthening character as well as an opportunity to learn from the surrounding environment. The research method used in this research is a quantitative descriptive method with a one group pre-test post-test design type of research. The population and sample in this research were PBSI students of the Indonesian Literature Language Education Study Program, FKIP, Al Washliyah Muslim Nusantara University. The sample in this study consisted of 30 semester 3A students taken in one class. Before carrying out cycle 1, an initial test was carried out first. In the initial test, an average score of 66.7 was obtained or a result assessment percentage (PPH) of 66.7%. The next step is to carry out the action in two cycles. In cycle 1, the average result (PPH) was 72.3%, higher than at the start of the test. But it has not yet met the target for implementing class actions. To achieve better learning, reflection is carried out for further action. Then continued cycle II with an average value (PPH) of 80.2%. The target output in this research is national/international journals or proceedings. Based on the results of this research, it is hoped that it will become information and input for lecturers and students, as well as the academic community and all parties so that they can use economical and efficient learning media effectively to achieve learning goals.